Association of Race, Ethnicity, and Socioeconomic Status With Esthesioneuroblastoma Presentation, Treatment, and Survival. Issue 1 (February 2022) - Sharma, Rahul K.; Irace, Alexandria L.; Overdevest, Jonathan B.; Turner, Justin H.; Patel, Zara M.; Gudis, David A.
Objective: Socioeconomic and other demographic factors are associated with outcomes in head and neck cancer. This study uses a national cancer database to explore how patient race, ethnicity, and socioeconomic status (SES) are associated with esthesioneuroblastoma outcomes, including 5-year disease-specific survival (DSS), conditional DSS, stage at diagnosis, and treatment. Study Design: Retrospective cohort analysis. Setting: Patients with esthesioneuroblastomas between 1973 and 2015 from the SEER registry (Surveillance, Epidemiology, and End Results). Methods: The National Cancer Institute Yost Index, a census tract–level composite score composed of 7 parameters, was used to categorize the SES of patients. Kaplan-Meier analysis and Cox regression were conducted to assess DSS. Conditional DSS was calculated per estimates from simplified Cox models. Logistic regression was conducted to identify risk factors for advanced cancer stage at diagnosis and the likelihood of receiving multimodal therapy. Results: Complete data were included for 561 patients. DSS was significantly associated with SES (log-rank, P < .01) but not race. According to Cox regression, DSS was worse for the lowest SES tertile vs the highest (hazard ratio, 1.70 [95% CI, 1.05-2.75]; P = .03). Patients of the lowest SES tertile exhibited an increased risk of advanced cancer stage at diagnosis as compared with the highest SES tertile (odds ratio, 1.84 [95% CI, 1.06-3.30]; P = .035). Black patients (odds ratio, 0.44 [95% CI, 0.24-0.84]; P = .011) were less likely than other patients to receive multimodal therapy. SES alone was not associated with receiving multimodal therapy. Conclusion: SES is significantly associated with DSS and conditional DSS for patients with esthesioneuroblastomas. Inequalities in access to care and treatment likely contribute to these disparities.